PROBLEMS IN TEACHING ENGLISH - Imamaliyeva Gulnoza Ulug‘bekovna (Bright Mind Publishing, 2025)
This article analyzes the main problems that we encounter in the English language teaching process. In particular, factors such as low motivation of students, insufficient methodological tools, lack of environment and need for language are highlighted. Also, attention is paid to the teacher's experience, the level of use of modern technologies and the interactivity of the course content. Suggestions and recommendations for troubleshooting problems are also presented.
Keywords: English, teaching problems, motivation, methodology, modern technologies, language environment, interactive learning.